2005
DOI: 10.1007/s10265-005-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Diel changes in the CO2 exchange rates of reproductive organs of the tropical tree Durio zibethinus

Abstract: The daily variations in the in situ CO(2) exchange of the reproductive organs of Durio zibethinus trees, growing in an experimental field at University Putra Malaysia (UPM), were examined at different growth stages. Reproductive organs emerged on the leafless portions of branches inside the crown. The photon flux densities (PFD) in the chambers used for the measurements were less than 100 mumol m(-2) s(-1) and were 40% of the PFD outside of the crown. The daytime net respiration rate and the nighttime dark res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The fruits of some evergreen tree species have photosynthetic activity, although their contribution is generally low (Ogawa et al . , Imai & Ogawa ). Dipterocarp fruit wings have low photosynthetic ability (Kenzo et al .…”
Section: Amount Of Reproductive Organs Number Of Days With 30鈥恉ay Momentioning
confidence: 94%
See 1 more Smart Citation
“…The fruits of some evergreen tree species have photosynthetic activity, although their contribution is generally low (Ogawa et al . , Imai & Ogawa ). Dipterocarp fruit wings have low photosynthetic ability (Kenzo et al .…”
Section: Amount Of Reproductive Organs Number Of Days With 30鈥恉ay Momentioning
confidence: 94%
“…Ichie et al (2005a) also found that the carbon requirement during the fruit maturation stage is quite high in a dipterocarp tree. The fruits of some evergreen tree species have photosynthetic activity, although their contribution is generally low (Ogawa et al 2005, Imai & Ogawa 2009). Dipterocarp fruit wings have low photosynthetic ability (Kenzo et al 2003).…”
mentioning
confidence: 99%
“…Temperature and PAR positively affected the reproductive organs at stage one and seed status (Figure 2c, d, 4c, d). The respiration rates of both reproductive organs and whole plants generally increase with high temperature, and increased plant growth is evident at optimal temperatures (Flanagan & Johnson 2005, Ogawa et al 2005. Increased PAR tends to increase fruit set and seed weight in mature fruits (Figueroa-Castro & Valverde 2011, Zhang et al 2005.…”
Section: Resource Limitation Of the Reproductive Success And The Resomentioning
confidence: 99%
“…Other reports suggest that reproductive organs such as fruits have photosynthetic activity and are able to re-fix CO 2 in woody plants growing in boreal (Linder and Troeng 1981;Koppel et al 1987), temperate (Bazzaz et al 1979;Ogawa et al 1988;Pavel and DeJong 1993;Proietti et al 1999;Ogawa and Takano 1997;Wang et al 2006), and tropical (Cipollini and Levey 1991;Whiley et al 1992;Ogawa et al 1996;Kenzo et al 2003;Ogawa et al 2005) regions. It is therefore important to consider CO 2 re-fixation by fruit photosynthesis when discussing the carbon balance.…”
Section: Introductionmentioning
confidence: 95%